Bio-inspired fabrication of high perm-selectivity and anti-fouling membranes based on zwitterionic polyelectrolyte nanoparticles. Issue 11 (26th February 2016) - Ji, Yan-Li; An, Quan-Fu; Guo, Yao-Shen; Hung, Wei-Song; Lee, Kueir-Rarn; Gao, Cong-Jie
Abstract : Biologically inspired TFN membranes incorporated with zwitterionic polyelectrolyte nanoparticles exhibit high perm-selectivity and anti-fouling properties. Abstract : Nanofiltration membranes featuring high permeability, selectivity and anti-fouling properties represent a focal point of advanced membrane technologies for clean water production and purification. Inspired by "water channel" structures and fouling resistance characteristics of biological membranes, we fabricated a novel thin-film nanocomposite (TFN) membrane containing zwitterionic polyelectrolyte nanoparticles (ZPNPs) by interfacial polymerization, wherein ZPNPs act as building blocks allowing for simultaneously improved permeability, selectivity and anti-fouling properties. By modulating the zwitterionic group content and ionic cross-linking degree of ZPNPs, the TFN-ZPNP membrane showed high water permeability (109.7 L m −2 h −1 MPa −1 ) and enhanced NaCl/Na2 SO4 selectivity (28.4), respectively; these values were 191% and 125% of those for the pristine polyamide membrane. It was also demonstrated that the incorporation of ZPNPs can increase the surface hydrophilicity, electronegativity and reduce the surface roughness, leading to an improved anti-fouling performance against the bovine serum albumin protein foulant.